PERCENTAGE BODY FAT OF SECONDARY SCHOOL ADOLESCENTS IN IBADAN NORTH LOCAL GOVERNMENT AREA, NIGERIA (2013)
Adolescence is a transitional phase from childhood to adulthood during which significant changes in body composition occur with a tendency towards excessive fat accumulation. Determining body fat proportions at this stage of life could give an insight into the need for early intervention. The actual body fat estimates of school adolescents have not been adequately researched in Nigeria. This study was carried out to determine the Percentage Body Fat (PBF) of secondary school adolescents in Ibadan North Local Government Area, Nigeria. Using a three-stage random sampling method, 623 adolescents aged 10 to 19 years were selected from two private (141) and six public (482) secondary schools in a cross sectional study. A validated, structured interviewer-administered questionnaire was used to collect data on socio-demographic characteristics. Parents’ socioeconomic status was grouped as high, middle and low using the combination of level of education and occupation. The PBF was assessed using a Bioelectric Impedance Analyser (BIA). The participants’ PBF for age and sex were classified as low <5th, normal 5th – 95th and high >95th percentiles of the study population respectively. Data were analysed using descriptive statistics, Chi-square test, Student’s t-test, ANOVA and Pearson Correlation. Overall mean age was 14.5±2.1 years and 60.0% were female. The participants were from families in low (19.6%), middle (51.7%) and high (28.7%) socioeconomic categories. Overall, mean PBF was 12.6±7.1%. Mean PBF for male 8.5±5.6% was lower than 14.9±6.7% for female (p<0.05). There was no significant correlation between PBF and age among female (r = 0.064, p>0.05) but a significant negative correlation was observed among male participants (r = -0.224, p<0.05). Among male participants, mean PBF of low (7.8±5.2%), middle (8.3±5.5%) and high (9.2±6.1%) socioeconomic status were not significantly different (p>0.05). Similarly, there were no differences in the mean PBF of low (15.2±6.9%), middle (14.8±6.9%) and high (14.9±6.7%) socioeconomic status among female participants (p>0.05). Proportion of adolescent PBF <5th and >95th percentiles were 3.9% and 19.9% respectively. Prevalence of PBF >95th percentile was higher among male (28.1%) than female (14.4%) adolescents (p<0.05). Slightly more female participants (4.3%) than male (3.2%) had PBF <5th percentile (p<0.05). More male participants in public (31.8%) compared with 15.8% among those in private schools had PBF >95th percentile (p<0.05). There was no significant difference in prevalence of PBF >95th percentile among female participants in private (10.7%) compared with those in public schools (15.5%). There was no significant difference in the proportion of respondents who had PBF >95th percentile in low (20.5%), middle (22.4%) and high (15.1%). Similarly, proportions of participants with PBF <5th percentile in low, middle and high socioeconomic groups were 3.3%, 4.3% and 3.4% respectively were not significantly different. Male adolescents were likely to rise above 95th percentile of percentage body fat estimates for age and sex irrespective of socioeconomic status especially in public school. There is the need to initiate programmes that may enhance early identification of adolescents with the tendency of accumulating excess fat.